(3GdfXe GdVQjHjI (B/s - (3GdHWQjb, jhfS CMeOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3aj gPG GdcJGH CgejI OQGSI GdfXe GdVQjHjI hechfGJgG , JCKjQ GdhGbY GdGbJUGOj hGdSjGSj hGdGLJeGYjI aj GdfXe GdVQjHjI , OhQ GdSjGSI GdVQjHjI aj JMbjb GdGgOGa GdGbJUGOjI GdGLJeGYjI , OhQ GdSjGSI GdVQjHjI aj JMbjb GdGgOGa GdGbJUGOjI hGdGLJeGYjI , fTCI hbGfhfjI GdVQjHI , fWGb JWHjb GdbGfhf GdVQjHj heTGcdI GdVQjHI Ydi ONd GdGTNGU GdWHjYjjf , GdVQjHI Ydi GdTQcGJ , VQGFH GdKQhI hGdGfaGb , GdfXGe GdVQjHj GdeUQjs
Keywords: (3GdVQGFHs